CRISIS COMMUNICATION AND RISK PERCEPTION: REPUTATION RISK MANAGEMENT STRATEGIES IN THE SOCIAL MEDIA ERA - Costa, Rizky Oktarina (PT. Hafasy Dwi Nawasena, 2025)
The phenomenon of crisis communication in the social media era demands fundamental changes in organizational reputation management strategies. This study aims to construct a new conceptual model that explains the relationship between crisis communication, public risk perception, and digital ethics-based reputation management. Using a qualitative approach based on a systematic literature review, this study examines more than 60 Scopus and SAGE-indexed scientific publications (2015–2024) to identify conceptual patterns and research gaps. The analysis shows that traditional crisis communication models oriented towards message control are no longer effective in dealing with the two-way communication structure of social media. Public risk perception is now mediated by the dynamics of collective emotions and engagement algorithms, which demand an empathy- and data-driven communication approach. This study proposes an Ethical Data-Driven Reputation Management (EDDRM) model that integrates three main dimensions: data analytics, public communication ethics, and social empathy. This model has implications for strengthening organizational social legitimacy through transparency, adaptive speed, and moral integrity. The study's main contribution lies in updating the crisis communication paradigm oriented towards public trust and balancing strategic effectiveness with ethical responsibility in the contemporary digital ecosystem.